Dispersion Compensation In Optical Communication - A Review. - Sharma, Er. Abhishek; Singh, Er. Sukhbir; Sharma, Er. Bhubneshwar (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Dispersion is defined as - the phenomenon in an optical fiber whereby light photons arrive at a distant pointÂ  in the different phase then they entered the fiber. Dispersion causes signal distortion that ultimately limits the bandwidth and usable length of the fiber cable. Therefore dispersion compensation (management) becomes an essential part to study in optical communication for better transmission. In this paper we have reviewed the various techniques (schemes) that are used for dispersion compensation.